Present status of the native parthenogenetic strain of Artemia sp. in the salterns of Tamil Nadu - Sivagnanam, S; Krishnakumar, V; Kulasekarapandian, S; Munuswamy, N (Indian Journal of Fisheries, 2012)
This article reports on a field survey conducted on the occurrence of the brine shrimp, Artemia in salt pans and lakes in Tamil Nadu, south-east coast of India during 2002–2003. A total of 15 salt pans in four regions were sampled; the maximum samplings were carried out from Tuticorin region. The reproductive performance of the locally colonized Artemia populations, both parthenogenetic and bisexual forms were assessed. Based on the available field data, a chart on the sources of native (parthenogenetic) and bisexual strains of Artemia in Tamil Nadu was prepared. Native parthenogenetic populations were found to occur in Vedaraniyam (VRM) and Nagercoil (NGC) regions, whereas bisexual populations of Artemia were predominant in Chennai (CHE) and Tuticorin (TCN) regions. The present study emphasizes the need for conservation of the native parthenogenetic strains by inoculating them in Artemia free salt pans.